2016
DOI: 10.1667/rr14202.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization by PARP Inhibition in DNA Repair Proficient and Deficient Tumor Cells: Proliferative Recovery in Senescent Cells

Abstract: Radiotherapy continues to be a primary modality in the treatment of cancer. DNA damage induced by radiation can promote apoptosis as well as both autophagy and senescence, where autophagy and senescence can theoretically function to prolong tumor survival. A primary aim of this work was to investigate the hypothesis that autophagy and/or senescence could be permissive for DNA repair, thereby facilitating tumor cell recovery from radiation-induced growth arrest and/or cell death. In addition, studies were desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
90
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 91 publications
13
90
1
Order By: Relevance
“…Our laboratories have confirmed that PARP inhibitors do not increase radiation-induced apoptosis in HCT-116 colon carcinoma cells, but instead markedly enhance growth arrest and senescence (18). In this context, a tumoristatic effect could be considered a less desirable outcome than a tumoricidal effect since we have further determined that the growth arrest induced by radiation with PARP inhibition is transient (as is also the case with that induced by radiation alone) (18) in at least a fraction of the cells.…”
Section: Increase In Dna Damagementioning
confidence: 77%
See 4 more Smart Citations
“…Our laboratories have confirmed that PARP inhibitors do not increase radiation-induced apoptosis in HCT-116 colon carcinoma cells, but instead markedly enhance growth arrest and senescence (18). In this context, a tumoristatic effect could be considered a less desirable outcome than a tumoricidal effect since we have further determined that the growth arrest induced by radiation with PARP inhibition is transient (as is also the case with that induced by radiation alone) (18) in at least a fraction of the cells.…”
Section: Increase In Dna Damagementioning
confidence: 77%
“…In this context, a tumoristatic effect could be considered a less desirable outcome than a tumoricidal effect since we have further determined that the growth arrest induced by radiation with PARP inhibition is transient (as is also the case with that induced by radiation alone) (18) in at least a fraction of the cells. Although recovery of the culture as a whole could reflect outgrowth of a few undamaged or lightly damaged cells rather than proliferation of transiently arrested, senescent cells, we have succeeded in separating from the treated cultures β-galactoside-expressing cells that appear morphologically senescent, yet resume proliferation after a short delay (18). …”
Section: Increase In Dna Damagementioning
confidence: 99%
See 3 more Smart Citations